PENINGKATAN KETERAMPILAN MENULIS PENGUMUMAN MELALUI MODEL NUMBERED HEADS TOGETHER DENGAN MEDIA SURAT KABAR (Joyful Learning Journal, 2015)
Tujuan penelitian ini adalah untuk mendeskripsikan peningkatan keterampilan guru, aktivitas siswa, danketerampilan menulis pengumuman pada kelas IV C SDN Petompon 02 Semarang dengan menerapkan modelpembelajaran NHT dengan media surat kabar. Penelitian ini adalah penelitian tindakan kelas yang terdiri dari 3siklus dengan tahapan perencanaan, pelaksanaan, pengamatan dan refleksi. Subjek penelitian adalah guru dansiswa kelas IV C SDN Petompon 02 Semarang berjumlah 41 siswa. Hasil penelitian menunjukkan bahwa: (1)keterampilan guru mengalami peningkatan, pada siklus I memperoleh skor 27 kategori baik, siklus II memperolehskor 30 kategori baik, siklus III memperoleh skor 35 kategori sangat baik, (2) aktivitas siswa mengalamipeningkatan, pada siklus I memperoleh rata-rata skor 22,9 kategori baik, siklus II memperoleh rata-rata skor 25,07kategori baik, siklus III memperoleh rata-rata skor 28,62 kategori baik (3) persentase ketuntasan klasikal jugamengalami peningkatan, pada siklus I sebesar 52,5% kualifikasi tidak tuntas, siklus II sebesar 75,6% kualifikasituntas, pada siklus III sebesar 89,5% kualifikasi tuntas. Simpulan dari penelitian ini adalah melalui modelkooperatif tipe NHT dengan media surat kabar dapat meningkatkan keterampilan guru, aktivitas siswa danketerampilan menulis pengumuman pada siswa kelas IV C SDN Petompon 02Semarang The background of the study was based on the pre-observation conducted at the fourth C grade of SDN Petompon02 Semarang. The teacher did not use learning innovation so that the students were not motivated to take part inthe class activity. The students learning outcomes were mostly under the minimum passing grade criteria.Therefore, the study on the use of NHT model with newspaper was conducted. This study aimed to improveteacher’s skill, students’ activity, and students’ learning outcomes in writing announcement skill learning at thefourth C grade of SDN Petompon 02 Semarang. The design of the study was classroom action research in threecycles with the stages of planning, action, observation, and reflection. The subjects of the study were teacher and41 students of the foruth C grade of SDN Petompon 02 Semarang. The results of study showed: 1) teacher’s skillin the first cycle obtained the score of 27 (good), in the second cycle obtained the score of 30 (good), and in thethird cycle obtained the score of 35 (very good), 2) the students’ activity in the first cycle gained the average scoreof 22.9 with a good category, in the second cycle gained the average score of 25.07 with a good category, and inthe third cycle gained the average score of 28.62 with a very good category, 3) The percentages of students’ learningoutcoomes in the first cycle obtained classical achievement of 52,5% with a not passed qualification, in the secondcycle obtained 75,6 % with a passed qualification, and in the third cycle obtained 89.5 % with a passed qualification.The study concluded that the use of cooperative learning NHT model with newspaper could improve teacher’sskill, students’ activity, and announcement writing skill of the fourth C grade students of SDN Petompon 02Semarang.